There Is No Escape: What Google Can Teach Instruction Librarians. - Kathleen Gregory (Issues in Science and Technology Librarianship, 2013)
The article comments on the influence of Google on the library science in the U.S. The author reflects on her experience as an instruction librarian at the University of Denver in Colorado. She observes the adoption of discovery systems by a rising number of libraries to provide users a Google-like search experience. The application of Google's education strategy is suggested for teaching library science.